Etiology and prevalence of macadamia diseases in Brazil - Silva, R. [UNESP]; Nechet, K. L.; Moriya, L. M.; Carvalho, V. N. [UNESP]; Biafora, M. R.; de Souza, D. E.H.; Halfeld-Vieira, B. A. (Springer Nature, 2024)
In Brazil, the cultivation of macadamia (Macadamia integrifolia) has expanded within the nut industry. However, there is a lack of information concerning the primary macadamia diseases under Brazilian conditions, which is crucial to defining management strategies. This study aims to identify the causal agents responsible for macadamia diseases and determine their prevalence based on a 2-year survey in a representative production area in Brazil. Samples were collected from leaves, trunk sections, racemes, and macadamia fruit from November 2019 to September 2021 in Brazil. All associated microorganisms were isolated, and pathogenicity tests were conducted to fulfill Koch’s postulates. For isolates confirmed as pathogenic, morphological characterisation and molecular identification were performed. The diseases observed, along with their respective prevalence, were as follows: leaf spot caused by Neopestalotiopsis (7%), stem canker caused by Lasiodiplodia (28%), Cladosporium blight caused by Cladosporium (72%), and fruit rot caused by Colletotrichum (18%). This study marks the first reporting of the fungi species L. pseudotheobromae, C. xanthochromaticum, and Co. siamense as phytopathogens of macadamia in Brazil. Additionally, it reports C. xanthochromaticum and Co. siamense for the first time as causal agents of Cladosporium blight and fruit rot in macadamia worldwide, respectively.
Keywords: Aetiology; Diagnostics; Epidemiology; Flower blight; Tree nut